Systematic analysis and prediction of the burden of Alzheimer’s disease and other dementias caused by hyperglycemia - He, Dongying; Liu, Manting; Tang, Yujin; Tian, Xiaona; Zhou, Lisi; Chen, Yizhen; Liu, Xiaoxia (Frontiers in Public Health, 2025)
BackgroundAlzheimer’s disease and other dementias (ADOD) pose a significant and escalating global public health challenge, particularly among the aging populations. Emerging evidence has identified high fasting plasma glucose (HFPG) as a major modifiable risk factor for ADOD, linking impaired glucose metabolism to cognitive decline and neurodegeneration. Despite this association, the comprehensive impact of HFPG on the global burden of ADOD has not been fully elucidated. Understanding the extent to which HFPG contributes to ADOD is crucial for developing targeted interventions and optimizing healthcare resource allocation to address this growing concern.MethodsUsing Global Burden of Disease data (GBD 2021), we analyzed the global HFPG-related ADOD burden from 1990 to 2021 using an age-period-cohort framework and predicted trends for 2050. A Shiny platform was developed to visualize the disease burden and trends across 204 countries and regions.ResultsIn 2021, approximately 15% of ADOD deaths and disability-adjusted life years (DALYs) were attributed to HFPG, a 271.05% increase from 1990. The incidence rate rose from 47.07 to 66.42, indicating poor control. The mortality rate from HFPG-ADOD increased by 305.81%. The primary burden was among the 80–84 age group. Trends in ASDR and ASMR showed an increase across most SDI regions, except Low SDI. Decomposition analysis and the APC model indicated poor control in high SDI regions due to aging populations over the past 5 years. By 2050, the global prevalence is projected to reach 1,003,018.047 (26124.40377, 12114480.49), with 345,342.5738 (1431.57781, 6022119.213) males and 657,675.4731 (24692.82596, 6092361.28) females. The Shiny platform predicts a yearly increase in ASDR and ASMR for HFPG-ADOD in China, which is consistent with GBD platform trends. The platform is accessible at http://116.196.73.86:3838/GBD/HFPG-ADOD/.ConclusionThe global burden of HFPG-related ADOD has been increasing, even in high SDI regions, over the past 5 years and is expected to continue rising until 2050. Implementing appropriate health policies to mitigate this trend could significantly reduce the substantial burden caused by HFPG-induced ADOD. Promoting the use of the Shiny prediction platform will contribute significantly to global healthy aging.